Nanoparticles and refractory organic matter: Interactions and consequences. Issue 4 (December 2015) - Delay, Markus; Schwegmann, Heiko; Frimmel, Fritz H.
Abstract: The broad application of engineered nanoparticles (ENP) will inevitably lead to their increased discharge into the environment, especially into aquatic systems. There, they meet refractory organic matter (ROM) of the humic type which is ubiquitous. In this contribution, the physical, chemical and microbiological interactions between ENP and ROM were investigated using nanoparticulate maghemite ( γ -Fe2 O3 ), SiO2 with positive (e.g. >Al + ) and negative (OH) surface charge, TiO2 (P25; ratio of anatase/rutile = 3:1), self-synthesised silver nanoparticles (n-Ag), ROM from a brown water lake and different microorganisms (MO). The physical interaction of ENP and ROM under well-defined conditions followed the Langmuir equation. Zeta potential (ZP) of the (nano)particles changed with ROM concentration and pH value of the solution. Photocatalytically active TiO2 –NP generated OH-radicals for the degradation of ROM via low molecular size intermediates. Finally, the toxicity of ENP for microbiological cells was quantified with EC50 values. Generally, the presence of ROM led to a distinct detoxification. All these results allow a deeper understanding of the principles of interactions between ENP and ROM. In particular, they are relevant to understand the environmental impact of ENP and to contribute to their beneficial application in technical systems.